Temporal trends of the incidence rate of syphilis during pregnancy and congenital syphilis in São Paulo, Brazil, 2011-2023 - Beatriz Poddis Busquim e Silva; Fernanda Penido Matozinhos; Rafaela Siqueira Costa Schreck; Fernanda Marçal Ferreira; Camilla Pontes Bezerra; Bárbara Tideman Sartório Camargo; Thales Philipe Rodrigues da Silva (Epidemiologia e Serviços de Saúde)
ABSTRACT Objective To analyze trends of syphilis during pregnancy and congenital syphilis, based on reported cases in São Paulo, Brazil, from 2011 to 2023. Methods Ecological time series study, based on data from Notifiable Health Conditions Information System records. The Prais-Winsten method was used to verify trends. Results 125,776 cases of syphilis during pregnancy and 42,418 cases of congenital syphilis were reported. Average annual percentage change (95%CI) in the syphilis during pregnancy incidence rate was 18.68 (95%CI 16.57; 20.84), pvalue < 0.001; while for congenital syphilis it was 11.99 (95%CI 7.00; 17.22), p-value < 0.001. Conclusion Incidence rates of syphilis during pregnancy and congenital syphilis showed significant increasing trends, which may be related to the increase in the former during the diagnosis period (1st trimester), demonstrating increased testing among pregnant women, clinical classification at the time of diagnosis (latent syphilis), as well as inefficiency of adequate treatment when diagnosis is late.